Early stages of perceptual face processing are confined to the contralateral hemisphere: Evidence from the N170 component. (March 2015) - Towler, John; Eimer, Martin
Abstract: High-level visual object processing is often assumed to be largely position-independent. Here we demonstrate that when faces and non-face objects simultaneously appear in opposite visual hemifields, the face-sensitive N170 component of the event-related brain potential (ERP) is exclusively generated in the contralateral hemisphere. The effects of face inversion on N170 amplitudes and latencies also show strong contralateral biases. These results reveal that retinotopic biases in low-level visual cortex extend well into category-selective high-level vision. We suggest that the contralateral organisation of face-sensitive visual processing results from generic competitive interactions between hemispheres during the simultaneous perception of visual objects.